(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Another form of the discrete mKdV hierarchy with self-consistent sources is given in the paper. The self-consistent sources are presented only by the eigenfunctions corresponding to the reduction of the Ablowitz-Ladik spectral problem. The exact soliton solutions are also derived by the inverse scattering transform.